Preparation of Financial Statements On Bpr Xyz Based On Sak – Etap - Yusuf; Annisa Aulia (PT FORMOSA CENDEKIA GLOBAL, 2022)
The financial report is a form of accountability by the management of the company to internal and external parties. Seeing the importance in terms of usability, financial statements must be prepared based on applicable standards so that they can be interpreted with the same concept and understanding by users. BPR XYZ is a financial institution whose main activity is to distribute credit to the public, this credit can pose risks that can affect the sustainability of the business, therefore the implementation of its business must be based on the principle of prudence in providing healthy credit. This study aims to determine whether the application of BPR XYZ financial statements is in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK – ETAP) and BPR Accounting Guidelines. The method used in this research is descriptive qualitative. The Financial Accounting Standards for Entities Without Public Accountability (SAK – ETAP) were born with the aim of accommodating the needs of entities that do not have significant public accountability in running their business. With the correct procedure regarding the provision of credit, it can reduce the risk of non-performing loans. Thus, the existence of a good credit granting procedure is very important in order to create cooperation to build the company in accordance with the vision and mission.